Midline Incision of a Graft in Staged Hypospadias Repair–Feasible and Durable? - Tonnhofer, Ursula; Hiess, Manuela; Metzelder, Martin; Hebenstreit, Doris; Springer, Alexander (Frontiers in Pediatrics, 2019)
Purpose: In severe hypospadias staged repair is commonly used and it is regarded as feasible, safe and durable. In this article we want to describe the results of a modification of the staged repair: a midline incision of the graft during the second stage. Materials and Methods: This is a consecutive single team (2 surgeons) retrospective series. Between 2014 and 2017, 250 patients underwent hypospadias repair, among them 35 patients that had primary staged hypospadias surgery with completed first and second stage repair. 24 (68.6%) cases received a preputial skin graft and 11 (31.4%) buccal mucosa graft. Median age at first stage was 1.5 (0.5 – 22.1) years, mean time between first and second stage operation was 0.72 (0.4-1.76) years. Follow up rate was 100%, mean follow up period was 1.50 (0.4-3.8) years. Results: The total complication rate was 22.9%. In buccal mucosa repair the complication rate was 36.4% and in preputial graft repair the complication rate was 16.7%, respectively. In 23 patients (65.7%) during second stage urethroplasty a midline incision was performed (8 glandular graft, 15 penile graft, 6 at level of urethral opening). Complication rate in non-incised urethroplasty was 8.3%, in incision at glandular level 37.5%, in incision at penile level 13.3% and in incision at urethral opening 16.7%, respectively. Conclusions Two stage repair is the method of choice in the correction of severe hypospadias. In selected cases a midline incision of the graft is feasible and can be applied if needed. Randomized studies will be needed to evaluate the true benefit of incising the graft.